Effect of adding CPP-ACP into a daily-use toothpaste on remineralization of enamel white spot lesions - Shaghayegh Rafiei; Hossein Bagheri; Mohsen Gholizadeh; Ali Faramarzi Garmroodi; Aliakbar Hodjatpanah Montazeri; Abdolrasoul Rangrazi (Mashhad University of Medical Sciences, 2024)
Objective: The purpose of this study was to investigate the effect of adding CPP-ACP into a daily-use toothpaste on the remineralization of enamel caries lesions.Methods: Thirty enamel blocks were obtained from bovine incisors. Each specimen was divided into three equal parts. One-third of each block was coated with varnish to serve as a sound control area, while the remaining two-thirds underwent a demineralization process. After demineralization, another one-third of the surface was varnished, leaving only one-third of the enamel to undergo remineralization. The enamel blocks were divided into three groups (n=10), according to the remineralization treatment applied as follows: Group 1: fluoride-containing toothpaste, Group 2: CPP-ACP-containing toothpaste, and Group 3: fluoride- and CPP-ACP-containing toothpaste.  Remineralization was assessed through the Vickers microhardness test at various depths (20, 50, 120 and 200 µm). The data were analyzed by ANOVA and LSD test, and P< 0.05 was considered statistically significant.Results: There was a significant difference in remineralization efficacy between the groups at the depth of 20 µm (P 0.001). Pairwise comparisons revealed that the toothpaste containing both fluoride and CPP-ACP had a significantly greater microhardness than other experimental groups (P 0.05). No significant difference was observed between the study groups concerning microhardness at 50, 120 and 200 µm depths (P 0.05).Conclusions: CPP-ACP can serve as a suitable alternative to fluoride in daily-use toothpaste for enamel remineralization. The concurrent use of fluoride and CPP-ACP in toothpaste can generate a synergistic remineralizing effect at the enamel surface layer.